Demethylation and desulfonation of textile industry dye, Thiazole Yellow G by Aspergillus niger LAG - Paul O. Bankole; Adedotun A. Adekunle; Sanjay P. Govindwar (Biotechnology Reports, 2019)
Filamentous fungi perform tremendously in adsorption of dyes from polluted environment. In this study, Aspergillus niger LAG decolorized thiazole yellow G dye within 5 days. Scale up studies done revealed that maximum decolorization (98%) was achieved at a concentration (10 mg L−1), temperature (35 °C) and pH 6. The fungus exhibited significant inductions in laccase (71%) and lignin peroxidase (48%) respectively. Spectrometric analysis (UV–vis, HPLC and gas chromatography-mass spectrometry) was used in analyzing the degraded products of the dye. The GCMS analysis revealed the production of two metabolites; sodium 6-methyl-2-phenyl-1,3-benzothiazole-7-sulfonate and 2-phenyl-4,5-dihydro-1,3-thiazole after degradation of thiazole yellow G dye. A metabolic pathway of thiazole yellow G dye degradation by Aspergillus niger was proposed. Significant growth in plumule and radicle couple with an attendant increase in germination further confirmed the detoxified status of the dye after degradation. Keywords: Biodegradation, Aspergillus niger, Thiazole yellow G dye, Detoxification